Das übernatürliche Existential: in der Taufgnade begründeter Beginn der Gleichförmigkeit des Menschen mit Christus : ein neuer Blick auf die Genese eines Grundaxioms Karl Rahners - Rulands, Paul (Zeitschrift für katholische Theologie, 2001)
In the present article the author puts a new light on Karl Rahners wellknown axiomatic term "supernatural existential". By a profound study of the early writings (until 1950) the author elaborates the origin of the "supernatural existential". This origin is not to be found in Rahners early theology of grace, but in his (patristic inspired) theology of baptism. In fact, the article shows, that an adequately full understanding and reception of Rahners later "transcendental theology" is not possible without the knowledge of the neo-scholastic background of his early works, a fact which is nearly completely neglected in the actual mainstream Rahnerinterpretation.